A new species of Peritrox Bates, with a revised key for the genus (Coleoptera, Cerambycidae, Lamiinae) - Rodrigues, Juliana Mourão Dos Santos; Mermudes, José Ricardo M. (Zootaxa, 2011)
Peritrox insulatus sp. nov. is described and illustrated from Brazil (Rio de Janeiro, Angra dos Reis, Ilha Grande). A key to the five known species is provided. A previously unpublished photograph of the holotype of Peritrox denticollis Bates (type species of the genus) and a discussion with diagnoses of all species are provided to complement the study.